Background knowledge and epistemological access: Challenges facing Black women in a SET scholarship programme - Liccardo, Sabrina; Botsis, Hannah; Dominguez-Whitehead, Yasmine (South African Journal of Higher Education, 2016)
In promoting access to higher education in an unequal society there is a concern that universities operate in a manner that values background knowledge associated with those who have access to a privileged class location. We focus on background knowledge, its contribution to epistemological access to higher education and how such background knowledge is likely to affect Black women’s academic success. We analyse interviews with 19 Black women from socio-economically disadvantaged backgrounds who are recipients of a SET scholarship, utilising Ryle’s (1945) distinction between knowledge-how and knowledge-that, to understand their challenges in gaining epistemological access to university. Despite the scholarship programme’s comprehensive support, the findings suggest that students who enter with background knowledge acquired at well-resourced high schools are academically advantaged. We argue that SET scholarship programmes that recruit low-income students are necessary, but insufficient interventions for enabling epistemological access. Further responsiveness is required on the part of the university.